Оптимизация конструкции мембранных датчиков - Rubcevich, I. I.; Wysotsky, V. B.; Kovalchuk, N. S. (PE "Politekhperiodika", Book and Journal Publishers, 2009)
The possibility of reducing the power consumed by the gas concentration sensor through the introduction of cracks in the structure of the multi-layered membrane has been considered. The conduction of etching of the peaks of pores in concentrated orthophosphoric acid for increasing of the effected area of contact of platinum with sub layer of porous aluminium has been suggested.